Uji Toksisitas Akut Ekstrak Daun Ketepeng Cina (Cassia alata) pada Tikus (Rattus norvegicus) - Fadholly, Amaq; Ramadhan, Maharani Kartika (IPB University, 2025)
The leaves of Cassia alata exhibit potential properties as antioxidants, immunostimulants, antimicrobials, anti-dengue agents, and laxatives. This study aimed to determine the LD50 value of the administration of Cassia alata leaves extract using the Thompson-Weil method. A total of 25 rats (Rattus norvegicus) were utilized in the study, divided into five dose groups. One group served as the control (P0), receiving only distilled water, while the four treatment groups were administered doses of 500 (P1), 1000 (P2), 1500 (P3), and 2000 (P4) mg/kg BW. Toxic symptoms and changes in body weight were observed for 14 days. The results showed that there was one death at a dose of 1500 mg/kg BW and two deaths at a dose of 2000 mg/kg BW. The administration of Cassia alata leaf extract resulted in toxic symptoms, including reduced motor activity, respiratory difficulties, and weight loss. The LD50 value obtained was 1.9 g/kg BW. The extract of Cassia alata leaves exhibit a toxic effect on rats.